Revolutionizing construction safety: introducing a cutting-edge virtual reality interactive system for training US construction workers to mitigate fall hazards - Alzarrad, Ammar; Miller, Matthew; Durham, Luke; Chowdhury, Sudipta (Frontiers in Built Environment, 2024)
The construction sector is inherently hazardous, with falls from lofty positions being a primary cause of worker fatalities and injuries. The Occupational Safety and Health Administration (OSHA) has established stringent laws and requirements to protect construction workers. Traditional safety training methods have demonstrated limited effectiveness in adequately addressing and mitigating fall risks. However, Virtual Reality (VR) technological breakthroughs have created new opportunities for inventive safety teaching techniques. This study suggests using interactive VR technologies to offer construction workers immersive and highly efficient training in the crucial area of fall safety, guaranteeing compliance with OSHA regulations. This innovative training system merges the immersive capabilities of VR with the precise safety requirements set by OSHA, resulting in a complete and powerful instructional tool. An assessment was conducted to determine the effectiveness of the suggested virtual reality (VR) training. A total of eighty-two construction workers from two small enterprises took part in a case study. Company B employed VR as a method of instruction, whereas Company A utilized traditional training methods. Both groups were subjected to pre- and post-training evaluations, which consisted of six questions. The initial pre-training test did not reveal any significant disparities in the levels of knowledge between the two groups. Unlike the regular training group, the VR group exhibited a significant reduction in incorrect responses following the training sessions. Statistical studies have shown that VR training is more successful than traditional training techniques in reducing fall-related events in the construction sector. This conclusion is backed by a p-value of 0.0016, which is lower than the significance level of 0.05.